The learning styles and study behaviours of Anaesthetists in a postgraduate training programme - Mahomed, Sameerah (My University, 2017)
The Part I examination in anaesthesiology in South Africa has historically attracted a low average national pass rate of 50% or less. The medical and educational literature has shown that students’ approaches to learning, amongst other factors, may impact their educational and assessment outcomes. Therefore, the aim of this study was to describe the learning styles and study behaviours of anaesthetists in the postgraduate programme at Wits, particularly in the context of their preparation for the Part I examination. A prospective, cross-sectional, contextual, descriptive study was conducted amongst all anaesthetists who were on the Wits circuit, who had attempted the Part I examination from 2010 to 2015. A self-administered questionnaire was used for data collection. Measures were put in place to maintain confidentiality of the participants, as well as to ensure validity and reliability of the study. This study showed that anaesthetists at Wits were diverse in their approaches to learning, with average scores of 70% for deep learning, 67.8% for strategic learning and 60.8% for surface learning styles. Females were significantly more strategic than males (p=0.03) and those who had passed on first attempt at the Part I examination scored significantly higher on the “organised studying” sub-scale (p=0.048). This study further suggests that the anaesthetists may not necessarily be attuned to the requirements of adult learning when compared to their international counterparts in other disciplines. This may be a result of various academic and non-academic challenges cited by the anaesthetists in their experience with the Part I examination. In attempting to overcome these challenges, the anaesthetists had to adapt their study behaviours and develop effective coping mechanisms in order to be successful in the examination. This study further emphasises the need for constructive alignment within the adult educational system.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology.
Keywords: Learning Styles; Study Behaviours; Anesthetists